2004
DOI: 10.1038/nm1091
|View full text |Cite
|
Sign up to set email alerts
|

Role of inducible bronchus associated lymphoid tissue (iBALT) in respiratory immunity

Abstract: Bronchus-associated lymphoid tissue (BALT) is occasionally found in the lungs of mice and humans; however, its role in respiratory immunity is unknown. Here we show that mice lacking spleen, lymph nodes and Peyer's patches generate unexpectedly robust primary B- and T-cell responses to influenza, which seem to be initiated at sites of induced BALT (iBALT). Areas of iBALT have distinct B-cell follicles and T-cell areas, and support T and B-cell proliferation. The homeostatic chemokines CXCL13 and CCL21 are expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

57
746
8
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 693 publications
(817 citation statements)
references
References 38 publications
57
746
8
6
Order By: Relevance
“…and Mycobacterium tuberculosis bacteria, as well as influenza and hepatitis C viruses, have been linked with ELF development in mice and humans 77, 78, 79, 80, 81, 82, 83, 84. Interestingly, ELF formation in response to infection features at mucosal sites including lung, gastric and salivary gland tissues 78, 82, 85. ELFs that develop in response to microbiota are also important for maintaining intestinal homeostasis 86.…”
Section: Elfs As Inductive Sites For Anti‐pathogen Immune Responsesmentioning
confidence: 99%
See 2 more Smart Citations
“…and Mycobacterium tuberculosis bacteria, as well as influenza and hepatitis C viruses, have been linked with ELF development in mice and humans 77, 78, 79, 80, 81, 82, 83, 84. Interestingly, ELF formation in response to infection features at mucosal sites including lung, gastric and salivary gland tissues 78, 82, 85. ELFs that develop in response to microbiota are also important for maintaining intestinal homeostasis 86.…”
Section: Elfs As Inductive Sites For Anti‐pathogen Immune Responsesmentioning
confidence: 99%
“…There is considerable evidence linking ELFs with anti‐microbial and viral immunity. For example mice lacking spleen, lymph nodes and Peyer's patches mount robust B‐cell and T‐cell responses to influenza virus at sites of iBALT formation 82. Notably, in the absence of peripheral lymphoid organs, these mice tolerate higher virus doses than wild‐type mice, suggesting that the anti‐viral response generated at iBALT is not only protective but may also be less pathogenic than those generated in the periphery.…”
Section: Elfs As Inductive Sites For Anti‐pathogen Immune Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has, however, been reported that Tertiary Lymphoid Structures (TLS) are abundant in highly inflamed tissues resulting from chronic infections, auto-immune diseases or organ transplantation [38]. It has been demonstrated that efficient primary and secondary immune reactions can be generated in mice lacking lymph nodes [39,40]. In cancers, mature DC presenting tumor-associated antigens may migrate from the tumor to the draining lymph nodes and educate T and B lymphocytes [37].…”
Section: An Efficient Immune Reaction May Be Shaped At the Tumor Sitementioning
confidence: 99%
“…Chronic rejection after lung transplantation is manifested by obliterative bronchiolitis (OB), a chronic inflammatory and fibroproliferative condition in small airways, and its clinical correlate, bronchiolitis obliterans syndrome (BOS) (10). In the lung, TLO is considered to be represented by an inducible form of bronchus-associated lymphoid tissue (BALT), namely iBALT (1,11). Formation of iBALT has been reported in various chronic inflammatory lung diseases such as emphysema (12), pulmonary fibrosis (13), and chronic hypersensitive pneumonitis (14).…”
mentioning
confidence: 99%